Effects of probiotic and Vitamin C on domestication and breeding performance of indigenous koi, Anabas testudineus under cage system (Journal of the Bangladesh Agricultural University, 2020)
An experiment was accomplished on domestication and induced breeding of indigenous climbing perch, Anabas testudineus. For domestication, fish were stocked and reared for six months in nine cages (each having 1.0 m3 in size) set in three ponds (Pond 1, 2 and 3) so that three cages were set up in each pond. Three supplementary feeds such as feed mixed with vitamin C, only supplementary feed and supplementary feed with probiotic (Bacilus subtilis and Aerobacter sp.) considered as treatment T1, T2 and T3, respectively were provided to triplicate cages in each pond and the cages were considered as replications R1, R2, R3. Highest growth in terms of net length and weight gain was found in T3 (9.35±2.65 cm and 44.58±4.68 g) followed by T1 (9.00±2.03 cm and 37.62±3.45 g), and T2 (6.18±1.57 cm and 34.24±3.08 g), respectively. Likewise, the highest average value of GSI was found in T3 (7.26±2.12) in the month of April while lowest average value of GSI (0.64±0.21) was found in T2 in the month of July. Three induced breeding trials were conducted using carp pituitary gland extract (PG) where female broods received 6-8 mgkg-1 body weight and males received 2-4 mg kg-1 body weight. Fish in T3 injected with PG 4 mgkg-1 for male and 8 mgkg-1 for female showed highest result in case of ovulation rate (96.67±5.77), fertilization rate (75.75±2.00%) and hatching rate (90.25±2.18%) followed by T2 (ovulation, 80±10%, fertilization, 70.25±2.22%, hatching and 85.65±1.80%) and T1 (ovulation, 73.33±5.77, fertilization, 66.23±1.56% and hatching, 72.75±2.06%).The survival rate of fry was highest in T3 (65.9±1.09%) followed by T2 (60.75±2.00%) and T1 (55.5±2.46%). It was observed that, the mixture of probiotic with feed was more suitable for higher growth and GSI. 2.0 g probiotic (VC-7, Team aqua corporation, Taiwan) and 20 g molasses for 5 L of water were found better result for induced breeding of A. testudineus.J Bangladesh Agril Univ 18(1): 145–151, 2020https://doi.org/10.5455/JBAU.92166